Dissociable patterns of neural activity during response inhibition in depressed adolescents with and without suicidal behavior - Pan, Lisa A. (2011)
OBJECTIVES: Impaired attentional control and behavioral control are implicated in adult suicidal behavior. Little is known about the functional integrity of neural circuitry supporting these processes in suicidal behavior in adolescence. METHOD: We employed fMRI in 15 adolescent suicide attempters with history of major depressive disorder (MDD; ATT), 15 adolescents with history of MDD but not suicide attempt (NAT), and 14 healthy controls (HC), during performance of a well-validated GoNoGo response inhibition and motor control task that measures attentional and behavioral control, and has been shown to activate prefrontal, anterior cingulate and parietal cortical circuitry. Questionnaires assessed symptoms and standardized interviews characterized suicide attempt. RESULTS: A 3 group × 2 condition (“GoNoGo” response inhibition versus “Go” motor control blocks) block-design whole-brain analysis (p<0.05, corrected) revealed that NAT showed greater activity than ATT in right anterior cingulate gyrus (p=0.008), and that NAT, but not ATT, showed significantly greater activity than HC in the left insula (p=0.004) to GoNoGo response inhibition blocks. CONCLUSIONS: While ATT did not show differential patterns of neural activity from HC during GoNoGo response inhibition blocks, ATT and NAT showed differential activation of the right anterior cingulate gyrus during response inhibition. Our findings indicate that suicide attempt during adolescence is not associated with abnormal activity in response inhibition neural circuitry. The differential patterns of activity in response inhibition neural circuitry in ATT and NAT, however, suggest different neural mechanisms for suicide attempt versus MDD in general in adolescence that should be a focus of further study.